THE ROLE OF ISLAMIC CORPORATE GOVERNANCE, SHARIA SUPERVISORY BOARD, AND ISLAMIC SOCIAL RESPONSIBILITY IN COUNTERING FRAUDULENT FINANCIAL REPORTING - Media Kusumawardani; Achmad Soediro; Fardinant Adhitama; Vivi Usmayanti (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2025)
Fraudulent financial reporting occurs in Islamic companies, specifically Indonesian Islamic banks, which are well-developed and uphold religious values. Despite this commitment, fraud still occurs in Islamic banking institutions. Therefore, this study aimed to investigate variables capable of reducing the occurrence of financial statement fraud. It also aimed to examine the influence of Sharia aspects of Islamic banking, such as ICG, SSB, and Sharia Social Responsibility, on fraudulent financial reporting. To achieve these objectives, data were obtained from 125 samples from Islamic banking companies during the period 2012-2022. Logistic regression analysis was also conducted. The results showed that Islamic Corporate Governance had a positive influence on fraudulent financial reporting, while Sharia Supervisory Board and ISR had no significant influence on fraudulent financial reporting.